Pendidikan Inklusif Yang Berkeadilan: Analisis Literatur dan Implikasinya untuk Kebijakan Pendidikan - Dewi Hendayati; Caroline, Caroline; Firmansyah, Firmansyah (Jurnal Ilmiah Edukatif, 2025)
Inclusive and equitable education is an approach that aims to ensure that all students, regardless of physical, mental, social or economic limitations, have equal opportunities in the education system. The purpose of this article is to discuss the effectiveness and challenges of implementing inclusive education and its impact on education policy. The research method used is literature review. The results show that inclusive education brings significant benefits, not only for students with special needs but also for all students, by creating a supportive and diverse learning environment. Implementing inclusive education requires comprehensive and coordinated policies and support from various stakeholders including the government, educational institutions and communities. In addition, a paradigm shift and increased social awareness are essential to remove stigma and discrimination. Thus, inclusive education that is implemented effectively has the potential to realize a more equitable education system and socialize the perspective of diversity in the educational environment.